The Effect of Intellectual Capital, Firm Size and Capital Structure on Firm Performance, Evidence from Property Companies in Indonesia - Surjandari, Dwi Asih; Minanari, Minanari (Jurnal Dinamika Akuntansi, 2019)
The purpose of this study is to examine the effect of Intellectual Capital (represented by Human Capital Efficiency (VAHU), Physical Capital Efficiency (VACA), Capital Structure Efficiency (SCVA)), Company Size and Capital Structure on Company Performance (measured with ROA). The research sample is property sector manufacturing companies listed on the Indonesia Stock Exchange between 2013 and 2017, with a purposive sampling method and analysis with multiple regression using SPSS version 2.0. The results of the study show that: 1) VAHU and VACA have no significant effect on Company Performance, but SCVA has, 2) Company size has no significant effect on Company Performance, but 3) Capital Structure has. All of these variables together have a significant effect on Company Performance.